Treatment of acute Mania. (c1999) - Taissoun, Hala Issam (1999)
Background: Bipolar disorder is a relatively common disorder and is characterized by "unpredictable swings in mood from mania to depression". Mania is a disease state which induces difficulties in work performance and psychosocial functioning requiring rapid and effective treatment in order to allow the patients to return to nonnal function. It is a very serious illness characterized by a high rate of recurrence and a deteriorating course. The treatment of acute mania should not only be effective and well tolerated but also anticipate and modify the future course of illness. Lithium, anticonvulsants, antipsychotics and EeT are recognized treatments for acute marna. Although lithium is considered by most as the treatment of choice, the position of anticonvulsants and EeT is currently gaining ground. Objectives: This study is aimed at determining which treatment is most adequate for acute mania. ..... Each treatment modality will be discussed separately before comparing the three strategies for efficacy, safety and time taken to achieve the goals set. Methods and data analysis: All patients diagnosed with acute mama will be considered for this study. A non-randomized, open-label, comparative study will be conducted in a single center where patients will be assigned into three groups: the ones receiving lithium, the ones on anticonvulsants( carbamazepine or valproate) and fmally patients receiving EeT. Treatments are given depending on the patients' physician. All information concerning patients will be available through their files or medical records. The study data will be entered into a patient information database, using the SPSS Data Entry Program. Significance: Different studies have been conducted lately comparing various treatments of mania. Most of these have come out with contradicting results. So the question remains open as to which strategy should the first line treatment for acute mama. And because mania is such a severe disease with many complications, it would be interesting to find the answer.